2017
DOI: 10.3390/en10111773
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Modelling of Municipal Solid Waste Residues in a Pilot Scale Fluidized Bed Reactor

Abstract: Abstract:The present study investigates the hydrodynamics and heat transfer behavior of municipal solid waste (MSW) gasification in a pilot scale bubbling fluidized bed reactor. A multiphase 2-D numerical model following an Eulerian-Eulerian approach within the FLUENT framework was implemented. User defined functions (UDFs) were coupled to improve hydrodynamics and heat transfer phenomena, and to minimize deviations between the experimental and numerical results. A grid independence study was accomplished thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…These routines make use of a set of polynomial equations created to enhance the fluidization process, increasing the model's accuracy and predictability by minimizing deviations between the experimental and numerical results. Such UDF improvements were already confirmed and validated in previous works [4,20]. The five gasification runs, previously described in Section 2.2, using eucalyptus wood as a fuel and atmospheric air as gasification agent were also used to evaluate the model fitting regarding the different syngas composition species.…”
Section: Model Validation Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…These routines make use of a set of polynomial equations created to enhance the fluidization process, increasing the model's accuracy and predictability by minimizing deviations between the experimental and numerical results. Such UDF improvements were already confirmed and validated in previous works [4,20]. The five gasification runs, previously described in Section 2.2, using eucalyptus wood as a fuel and atmospheric air as gasification agent were also used to evaluate the model fitting regarding the different syngas composition species.…”
Section: Model Validation Resultssupporting
confidence: 63%
“…The heat absorption and thermal conductivity between the gas and the two solid phases were defined by implementing a UDF. This already implemented and validated routine adapts the default gas and solid phases heat absorption and transfer coefficient, by applying a set of polynomial equations designed to improve the gas-solid heat interactions [4,20].…”
Section: Energy Conservation Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Producer gas samples are then inserted into the chromatograph for further analysis within one hour after collection. Additional details on all remaining components are fully explained in [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Gasification of MSW has been proposed as energy conversion method. It was shown that the process could be enhanced when MSW is reduced to small particle sizes [6]. However, among others possible thermal treatments for energy recovery from waste, nowadays, combustion processes-in the following simply named WtE-are the most commonly widespread and applied for different types of waste, including MSW [7].…”
Section: Introductionmentioning
confidence: 99%